PENINGKATAN SIKAP PEDULI SOSIAL DAN PRESTASI BELAJAR MATA PELAJARAN PENDIDIKAN KEWARGANEGARAAN MELALUI MODEL KOOPERATIF TIPE STAD - Sitirah, Sitirah (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2019)
The background of this research is the lack of social care attitude and student’s achievement. This research is aimed to increase the social care attitude and student’s achievement in PKn (Civic) subject in the material of globalization effect through cooperative learning model of ( Student Teams Achievement Division)STAD type. The subject of research is the students of 4th grader of SD 02 Kedungwuluh Kidul with the total number of student are 16. Class action research was held in two cycles. Each of cycle consists of two meetings, one meeting consists of two hours. The procedure for each cycle included planning, action, observation, and reflection. The data collection was gotten from teacher’s observation and students’ activity report. To know the students’ social attitude, the researcher used social care attitude questionnaire. While to get the data of students’ achievement, the researcher used the evaluation sheet at the end of each cycle. Based on the research of social care attitude in cycle I, it was shown that the average was 3,20 and the percentage was 80,15% and from Cycle II, the average was 3,67 and the percentage was 91,87%. The result of achievement scoring from cycle I, the class average was 72,81 with the percentage81,25% and from the cycle, II was got the class average was 86,87 with percentage 100%. From those results, can be concluded that cooperative learning method (Student Teams Achievement Division)STAD type can enhance the social attitude care and students achievement of PKn of class IV SD 02 Kedungwuluh Kidul.